Adaptation and the Boundary of Multinational Firms - Costinot, Arnaud; Oldenski, Lindsay; Rauch, James (The Review of Economics and Statistics, 2011)
This paper offers the first empirical analysis of the impact of adaptation on the boundary of multinational firms. To do so, we develop a ranking of sectors in terms of “routineness” by merging two sets of data: ratings of occupations by their intensities in solving problems from the U.S. Department of Labor's Occupational Information Network and U.S. employment shares of occupations by sectors from the Bureau of Labor Statistics Occupational Employment Statistics. Using U.S. Census trade data, we demonstrate that the share of intrafirm trade tends to be higher in less routine sectors.